Biotechnological Advancements and Begomovirus Management in Okra (Abelmoschus esculentus L.): Status and Perspectives - Mishra, Gyan P.; Singh, Bijendra; Seth, Tania; Singh, Achuit K.; Halder, Jaydeep; Krishnan, Nagendran; Tiwari, Shailesh K.; Singh, Prabhakar M. (Frontiers in Plant Science, 2017)
Despite the importance of okra, as one of the important vegetable crop, very little attention has been paid to its genetic improvement using advanced biotechnological tools. The exploitation of marker assisted breeding in okra is often limited due to the availability of a few molecular markers, the absence of molecular genetic-map(s) and other molecular tools. Chromosome linkage-groups were not yet constructed for this crop and reports on marker development are very scanty and mostly hovering around cultivar characterization. Besides, very little progress has been observed for transgenic development. However, high throughput biotechnological tools like chromosome engineering, RNA interference (RNAi), marker-assisted recurrent selection (MARS), genome-wide selection (GWS), targeted gene replacement, next generation sequencing (NGS) and nanobiotechnology can provide a rapid way for okra improvement. Further, the etiology of many deadly viral diseases like the yellow vein mosaic virus (YVMV) and okra enation leaf curl virus (OELCV) in okra is broadly indistinct and has been shown to be caused by various begomovirus species. These diseases cause systemic infections and have a very effective mode of transmission; thus, preventing their spread has been very complicated. Biotechnological interventions have the potential to enhance okra production even under different viral-stress conditions. In this background, this review deals with the biotechnological advancements in okra per se along with the begomoviruses infecting okra, and special emphasis has been laid on the exploitation of advanced genomic tools for the development of resistant varieties.